2004
DOI: 10.1093/hmg/ddh187
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the IL10 gene reveals allele-specific regulation at the mRNA level

Abstract: Interleukin-10 (IL10) is a cytokine with key regulatory and anti-inflammatory function involved in the pathogenesis of various diseases. Although the large interindividual differences in the production of IL10 have been extensively associated with polymorphisms and haplotypes of the IL10 gene, surprisingly little evidence exists that this variation is actually dictated by IL10 haplotypes. Using the technique of allele-specific transcript quantification, the ratio between two alleles (A and G) of the IL10 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 22 publications
4
64
1
1
Order By: Relevance
“…In the present study, IL-1β/IL-10 plasma levels were significantly correlated to febrile seizures (Table 5; r=0.573; p<0.05) These inflammation cytokine (IL-1β) and anti-inflammation cytokine (IL-10) ratio correlation was inconsistent with [16] findings, but [11] study used IL-1β as an inflammation cytokine and IL-1RA as an anti-inflammation cytokine [16].…”
Section: Patient Characteristicscontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, IL-1β/IL-10 plasma levels were significantly correlated to febrile seizures (Table 5; r=0.573; p<0.05) These inflammation cytokine (IL-1β) and anti-inflammation cytokine (IL-10) ratio correlation was inconsistent with [16] findings, but [11] study used IL-1β as an inflammation cytokine and IL-1RA as an anti-inflammation cytokine [16].…”
Section: Patient Characteristicscontrasting
confidence: 78%
“…Dube et al (2000) [8] showed high doses of IL-1β are sufficient to generate seizures even without increased brain temperature [8,9]. There is an evidence of serial treatment of cells with LPS and ATP provides a very powerful stimulus to induce rapid and efficient release of IL-1β from monocytes, macro-phages and dendritic cells [10,11]. Research carried out by [5] found elevated levels of IL-1β in patients with febrile seizures when compared to normal ones, febrile patients without seizures and status epilepticus [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to IL2 and CD25, several other loci associated with human type 1 diabetes encode molecules that play a role in the immune regulation of T cell-mediated adaptive immune responses, or of inflammatory signals provided by the innate immune system [30]. These include IL-10 [16,37], IFIH1 [38,39], IL18RAP [40] and PTPN22 [41], which were able to stratify progression in our study. Although a number of type 1 diabetes-associated gene SNPs did not significantly add to the discrimination between the rapid and slow progressors (i.e.…”
Section: Discussionmentioning
confidence: 66%
“…Half life of IL10 mRNA in normal melanocytes is much shorter than in melanoma cell lines (7). Also, genetic variations in the 3Ј UTR of IL10 have been shown to be associated with IL-10 levels that could lead to disease pathogenesis (8,9). Therefore, a pellucid understanding of the posttranscriptional regulation of IL10 will be of scientific and clinical significance.…”
mentioning
confidence: 99%